The Role of Digital Literacy Programs in Bridging Digital Divide Gap among Middle-Aged Adults in Nigeria - Usman, M. (Journal of Research in Adult and Continuing Education, 2025)
As the world increasingly relies on digital technologies and industrial revolution, middle-aged adults face a growing risk of exclusion due to a lack of digital literacy. Digital divide disproportionately affects middle-aged adults, limiting their access to essential information, services, and social connections. This paper examines the concept of digital literacy, digital divide, middle-Age adults, forms of aging among middle-aged adults, digital divide among middle-aged adults, digital literacy programs for middle-aged adults, constraints of digital literacy programs for middle-aged adults, conclusion and recommendation.